2022
DOI: 10.1177/03331024221094293
|View full text |Cite
|
Sign up to set email alerts
|

Transorbital sonography: A non-invasive bedside screening tool for detection of pseudotumor cerebri syndrome

Abstract: Background Our objective was to assess optic nerve sheath diameter (a marker of elevated intracranial pressure) and optic disc elevation (a marker of papilledema) in pseudotumor cerebri syndrome using transorbital sonography. Methods The study was a prospective case-control study. We included patients with new-onset pseudotumor cerebri syndrome and matched healthy controls. All had fundoscopy, lumbar puncture with opening pressure and transorbital sonography. Sonography was assessed by a blinded observer. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Patients enrolled at RH served as the experimental group with bilateral fundus videos in all three situations. In addition, optic nerve sheath diameter (ONSD) was measured using transorbital sonography (TOS) before and after CSF drainage, as previously described (21). Papilledema grade was measured from the fundus photos in the IIH-group using Fris en grading (22).…”
Section: Methodsmentioning
confidence: 99%
“…Patients enrolled at RH served as the experimental group with bilateral fundus videos in all three situations. In addition, optic nerve sheath diameter (ONSD) was measured using transorbital sonography (TOS) before and after CSF drainage, as previously described (21). Papilledema grade was measured from the fundus photos in the IIH-group using Fris en grading (22).…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies [34,35] have looked at changes in optic nerve sheath diameter and optic disc elevation, as measured by orbital ultrasound Bscans, both showing a significant difference compared to healthy controls. B-scans can have potential variations resulting in a so-called 'blooming' effect, affecting measurement accuracy [36].…”
Section: Diagnosticsmentioning
confidence: 99%
“…After reading the full-text articles, 14 were further excluded. Finally, we identified 14 eligible studies [4][5][6][7][8][29][30][31][32][33][34][35][36] for inclusion in the systematic review and meta-analysis, comprising a total of 415 patients with IIH. The main characteristics of the included studies are presented in Table 3.…”
Section: Literature Search and Included Studiesmentioning
confidence: 99%
“…The risk of bias in included studies was assessed by the ROBINS-I tool 17 and is presented in Figure 3. All studies but one 34 presented a moderate or serious risk of bias, mostly due to the inclusion of patients with neurological diseases as controls [4][5][6]33,35 who also had significantly different baseline characteristics compared to the cases. 4,6,29,32,33 Lumbar puncture in controls was not performed in six studies, 6,[30][31][32][33]35 thus normal ICP could not be confirmed by measuring the opening pressure.…”
Section: Quality Control Of Included Studiesmentioning
confidence: 99%